Inter-subjectivity of khalwat (suluk) members in the tarekat Naqsyabandiyah Khalidiyah Ponorogo - S Maryam Yusuf (Indonesian Journal of Islam and Muslim Societies, 2020)
Naqshbandiyah is one of the names of tarekat that still exist in the Islamic world for 8 centuries (12-20 AD) because it has successfully carried out Islamization using cultural approach. Khalwat dar anjuman or ‘seclusion from the crowd’ is the main method of training and spiritual discipline to defend Islamic beliefs and values from the various crises of modern human life, which leads to spiritual emptiness.Assumption on khalwat causing someone to behave exclusively towards his/her environment is very interesting to study. Phenomenological research using Max Weber’s sociology of religion approach is used to find motives and symbolic meanings of student behavior (salik) that follow khalwat (suluk) in Tarekat Naqshbandiyah of Durisawo Ponorogo. The results of research show that, first,belief in kharisma murshid of Tarekat Naqsyabandiyah Khalidiyah is a gift from Allah SWT that is able to assist students in enhancing their spiritual experience (religious motives) and overcoming various problem that interfere both physical and psychological states, making them be more socially and morally intelligent in their lives (individual motives). Second, khalwat (suluk) has a subjective meaning for a student during his way to reach maqamat (station) until he is given the highest spiritual experience in the degree of ma’rifatullah by doing dhikr, muraqabah, kwayani, tawajuh, uzlah. Khalwat (suluk) also means intersubjective for salik during the interaction with murshid teacher through rabithah murshid, talqin, bai'at, sungkem tradition, and pilgrimage of murshid teacher’s grave. Third, the implication of students’ behavior after attending khalwat is they have calm and happy heart to be involved in social life in their environment according to their respective professions manifested in the form of social care in overcoming poverty and giving attention to orphans through daily social charity activities and donation. Khalwat participants have become intersubjective humans because they have been able to find their qualities in understanding reality.Naqsyabandiyah sebagai salah satu nama tarekat yang terbukti tetap eksis di dunia Islam selama 8 abad (12-20 M) karena berhasil melakukan Islamisasi dengan pendekatan kultural. Khalwat dar anjuman atau ‘menyepi di tengah keramaian’ sebagai metode utama pelatihan dan disiplin spiritual untuk mempertahankan keyakinan dan nilai-nilai Islam dari berbagai krisis kehidupan manusia modern yang menyebabkan kehampaan spiritual. Anggapan bahwa khalwat menyebabkan sesorang berikap ekskusif terhadap lingkungannya sangat menarik untuk diteliti.  Penelitian fenomenologis dengan pendekatan sosiologi agama Max Weber ini untuk menemukan motif dan makna simbolik dari perilaku murid (salik) yang mengikuti khalwat  (suluk) dalam tarekat Naqsyabandiyah Khalidiyah Durisawo Ponorogo. Hasil penelitian menemukan: pertama, kepercayaan pada kharisma mursyid tarekat Naqsyabandiyah Khalidiyah sebagai anugerah Allah SWT yang mampu membantu murid dalam meningkatkan pengalaman spiritualnya (motif agama) dan menyelesaikan beragam ujian, cobaan fisik dan psikis agar semakin cerdas secara social dan moral dalam kehidupannya (motif individu). Kedua, khalwat (suluk) memiliki makna subyektif bagi seorang murid dalam usahanya mencapai maqamat (station) hingga diberikan pengalaman ruhaniah tertinggi derajat ma’rifatullah dengan memperbanyak dzikir, muraqabah, kwajikan, tawajuh, uzlah,; dan khalwat (suluk) juga bermakna intersubyektif bagi salik melalui interaksinya dengan guru mursyid melalui rabithah mursyid, talqin, bai’at, tradisi sungkem, ziarah kubur guru mursyid. Ketiga, Implikasi perilaku murid setelah mengikuti khalwat adalah dengan hati yang tenang dan bahagia bisa terlibat dalam kehidupan sosial kemasyarakatan di lingkungannya sesuai profesi masing-masing diwujudkan dalam bentuk kepedulian sosial dalam mengentaskan kemiskinan dan perhatiannya kepada anak yatim melalui kegiatan amal sosial harian dan santunan. Peserta khalwat telah menjadi manusia yang intersubyektif, karena telah mampu mencari kualitas dirinya dalam memahami realitas.